Influência do sistema de disputa e nível dos adversários nas demandas físicas em atletas de elite do futebol brasileiro - Eliney Silva Melo (2020)
First division football teams compete in championships with simple elimination systems or straight points, and face opponents with different levels throughout the season. The aim of the study was to verify the influence of the dispute system and the level of the opposing team on the physical demands of elite Brazilian soccer players. The sample consisted of 41 professional soccer players, male, with an average age of 29.2 (± 4.8 years), body mass 78.5 (± 8.3 kg), height 179.3 (± 8, 8 cm), members of a team from the first division of the Brazilian Football Championship. The athletes' physical demands were monitored in the official matches of 2018 through a semi-automatic video system (InStat®) Moscow, Russia). The influence of the dispute system (study 1) was verified by comparing the variables: total distance traveled (DT); distance traveled at high speed; in sprints and the number of sprints, in the Mineiro and Copa do Brazil Championships. To verify the influence of the level of the opponents (study 2), the physical demands of the athletes in games against the first five (5) and the last five (5) teams in the final ranking of the Brazilian Championship were compared, using the same variables mentioned above. . The normality of the data was verified by the Shapiro Wilk test and the size of the Cohen’s d effect was calculated for the magnitude of the differences between comparisons. The reliability of the measurement instrument was tested using the Intraclass Confidence Interval (ICC 2.1). In study 01 in none of the variables, the presence of significant differences between the two competitions was evidenced. The results of study 2 showed a significant difference only in the variable DSPRINT [> 25.0 km / h] (p = 0.04, d = -0.48; small effect). For the analyzes, a significance level of p <0.05 was adopted and the SigmaPlot 11.0 statistical package (Systat Software Inc, USA) was used. The dispute system of the competitions evaluated did not influence the physical demand of an elite team of Brazilian football, however the level of the opposing teams influenced the physical demand in the distances covered in sprints.